Contemporary issues in economics - Parkin, Michael; Nobay, A. R.; Association of University Teachers of Economics (Manchester : Manchester University Press, 1975)
This volume contains a complete record of the annual proceedings of the [annual] conference of the Association of University Teachers of Economics (AUTE) held at the University of Warwick, in April 1973. The papers have been organized under three main headings: (1) 'Macro-economics'; (2) 'Allocation and efficiency' and (3) 'Growth, development, capital and trade'.
Proceedings of the [annual] conference of the Association of University Teachers of Economics, Warwick, 1973.
Includes bibliographical references and index.
rpm 19/09/2017
Loans
Keywords: Economics